2014
DOI: 10.1002/ente.201402099
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Water on the Performance of Calcium Oxide‐Based Sorbents for Carbon Dioxide Capture: A Review

Abstract: A technology using calcium oxide (CaO)‐based sorbents for CO2 capture has been identified to be the optimal candidate for capturing CO2 at high temperature. Realistic gases always contain water vapor and many other components, and it has been reported that these wet conditions have a non‐negligible influence on the performance of the sorbent. This Review outlines the role of H2O during the CO2 capture process using CaO‐based sorbents. The role of steam/H2O in sorbent reactivation, the effect of steam on carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 92 publications
0
21
1
Order By: Relevance
“…carbonation of CaO and the subsequent decomposition of CaCO 3 by calcination to regenerate the sorbent in order to be reused in a long-series cyclic process [13,14]. Addition of calcium oxide during gasification leads to breaking of thermodynamic equilibrium constraint and enhances hydrogen production [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…carbonation of CaO and the subsequent decomposition of CaCO 3 by calcination to regenerate the sorbent in order to be reused in a long-series cyclic process [13,14]. Addition of calcium oxide during gasification leads to breaking of thermodynamic equilibrium constraint and enhances hydrogen production [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [12] investigated the effect of limestone, olivine and dolomite on biomass gasification at temperature range of 750e850 C, and found that dolomite showed better performance in terms of catalytic activity on tar destruction. The capture of CO 2 is based on the carbonation of CaO and the subsequent decomposition of CaCO 3 by calcination to regenerate the sorbent in order to be reused in a long-series cyclic process [13,14]. Addition of calcium oxide during gasification leads to breaking of thermodynamic equilibrium constraint and enhances hydrogen production [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the overall trend, A + A1 showed the best effect on reducing the release of SO 2 . The reason was that 47.83% CaO existed in A1 (Table 2), and the reaction (4) happened as follows [16]. Therefore, A + A1 worked best…”
Section: Effect Of Additives On the So 2 Release Concentrationmentioning
confidence: 99%
“…Current research efforts to improve the utilization and durability of CaO‐based sorbents include i) the synthesis of calcium‐based sorbents from organic and inorganic precursors (instead of naturally derived CaO sources); ii) doping CaO with various metals; and iii) post‐treating the sorbents in an attempt to increase their lifespan . Studies by Martavaltzi et al on mixtures of mayenite, Ca 12 Al 14 O 33 , and CaO show that aluminum is an attractive additive to improve the stability of calcium oxides, albeit at the expense of the sorption capacity.…”
Section: Introductionmentioning
confidence: 99%